2008
DOI: 10.1063/1.2903486
|View full text |Cite
|
Sign up to set email alerts
|

Tin (IV) phthalocyanine oxide: An air-stable semiconductor with high electron mobility

Abstract: Air-stable n-type field effect transistors were fabricated with an axially oxygen substituted metal phthalocyanine, tin (IV) phthalocyanine oxide (SnOPc), as active layers. The SnOPc thin films showed highly crystallinity on modified dielectric layer, and the electron field-effect mobility reached 0.44cm2V−1s−1. After storage in air for 32days, the mobility and on/off ratio did not obviously change. The above results also indicated that it is an effective approach of seeking n-type semiconductor by incorporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Various metal phthalocyanines (MPcs) have been used in the fabrication of OFETs by vacuum deposition since the 1980s. [13][14][15][16][17][18][19][20][21] In the past several years, the mobility of MPcs has been dramatically improved by developing new fi lm-growth techniques and selecting an appropriate central metal ion. In particular, OFETs with a mobility > 1.0 cm 2 V − 1 s − 1 have been demonstrated with vanadyl phthalocyanine (OVPc) [ 17 ] and titanyl phthalocyanine (OTiPc).…”
Section: Doi: 101002/adma201004776mentioning
confidence: 99%
“…Various metal phthalocyanines (MPcs) have been used in the fabrication of OFETs by vacuum deposition since the 1980s. [13][14][15][16][17][18][19][20][21] In the past several years, the mobility of MPcs has been dramatically improved by developing new fi lm-growth techniques and selecting an appropriate central metal ion. In particular, OFETs with a mobility > 1.0 cm 2 V − 1 s − 1 have been demonstrated with vanadyl phthalocyanine (OVPc) [ 17 ] and titanyl phthalocyanine (OTiPc).…”
Section: Doi: 101002/adma201004776mentioning
confidence: 99%
“…In the WEG method, the inducing layer between the active layer and the substrate not only determines the quality of the active layer but also directly influences the device performances. For example, para ‐hexaphenyl ( p ‐6P), a typical inducing layer for fabricating high‐performance OTFTs,14, 16–18 is not suitable to fabricate organic solar cells because of the mismatch of its energy level and low carrier mobility.…”
Section: Summary Of the Cell Performance Extracted From I–v Curvesmentioning
confidence: 99%
“…For example, Kaji et al demonstrated recently for chloroaluminum phthalocyanine (ClAlPc) thin-films-based organic field-effect transistors (OFETs) that the Fermi level could be controlled widely in between the highest occupied molecular orbital (HOMO) and the lowest unoccupied MO of the films by applying an annealing procedure, and succeeded in tuning the type of charge carrier and the device performance. 23 Among several successful uses of polar molecules for organic devices, [23][24][25][26][27][28][29] the correlation between their film structures and the ELA is not yet well explored and thus still remains vague. For ultrathin films of various polar metal-Pc (p-MPc) molecules deposited on a molybdenum disulfide (MoS 2 ) (ClAlPc [30][31][32][33] ) and a highly oriented pyrolytic graphite (HOPG) (OTiPc, [34][35][36][37] OVPc, 38 ClAlPc, 39,40 and PbPc 41 ), we have thoroughly studied their film structure and growth, and evolution of electronic structure in these films using mainly ultraviolet photoelectron spectroscopy (UPS), metastable atom electron spectroscopy (MAES), and other electron spectroscopic methods.…”
Section: Introductionmentioning
confidence: 99%